Self-assembly of glycerol monooleate with the antimicrobial peptide LL-37: a molecular dynamics study - Innocenti Malini, R; Zabara, M; Gontsarik, M; Maniura-Weber, K; Rossi, R. M; Spano, F; Salentinig, S (RSC advances, 2020)
Over the past decade, the rapid increase in the incidence of antibiotic-resistant bacteria has promoted research towards alternative therapeutics such as antimicrobial peptides (AMPs), but their biodegradability limits their application. Encapsulation into nanocarriers based on the self-assembly of surfactant-like lipids is emerging as a promising strategy for the improvement of AMPs' stability and their protection against degradation when in biological media. An in-depth understanding of the interactions between the structure-forming lipids and AMPs is required for the design of nanocarriers. This in silico study, demonstrates the self-assembly of the amphiphilic lipid glycerol monooleate (GMO) with the antimicrobial peptide LL-37 into nanocarriers on the molecular scale. Molecular dynamics (MD) simulations show the formation of direct micelles, with either one or two interacting LL-37, and vesicles in this two-component system in agreement with experimental results from small-angle X-ray scattering studies. The hydrophobic contacts between LL-37 and GMOs in water appear responsible for the formation of these nanoparticles. The results also suggest that the enhanced antimicrobial efficiency of LL-37 in these nanocarriers that was previously observed experimentally can be explained by the availability of its side chains with charged amino acids, an increase of the electrostatic interaction and a decrease of the peptide's conformational entropy upon interacting with GMO. The results of this study contribute to the fundamental understanding of lipid-AMP interactions and may guide the comprehensive design of lipid-based self-assembled nanocarriers for antimicrobial peptides. Molecular dynamics simulations of glycerol-monooleate (GMO)/LL-37 nanocarriers show that hydrophobic interactions among the molecules drive the formation of GMO/LL-37 micelles.